2016
DOI: 10.1039/c6ra03890e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and preliminary therapeutic evaluation of copper nanoparticles against diabetes mellitus and -induced micro- (renal) and macro-vascular (vascular endothelial and cardiovascular) abnormalities in rats

Abstract: Current study synthesized and investigated the effect of low-dose copper nanoparticles (CuNPs) against diabetes mellitus and -induced experimental micro- (nephropathy) and macro-vascular (cardio and endothelium) complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…For example, CuNPs can be synthetized with a reduction of copper from a copper nitrate salt in the presence of iron, and to prevent the formation of larger sized CuNPs, the sample was continuously ultra-sonicated. The obtained nanoparticles sizes were recorded between 90 and 150 nm [38].…”
Section: Cementation Methodsmentioning
confidence: 99%
“…For example, CuNPs can be synthetized with a reduction of copper from a copper nitrate salt in the presence of iron, and to prevent the formation of larger sized CuNPs, the sample was continuously ultra-sonicated. The obtained nanoparticles sizes were recorded between 90 and 150 nm [38].…”
Section: Cementation Methodsmentioning
confidence: 99%
“…Modified response to ACh [6] and increased contraction to prostaglandin F 2 -alpha were observed [7] with no attenuation of endothelin-1-induced contraction [7]. Surprisingly, several studies have reported a beneficial anti-diabetic and cardioprotective role of CuNPs with a decreased production of inflammatory mediators [8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 97%
“…ROS mediated disruption may increase the release of CKMB, LDH and cTnI enzyme into the serum. 16,31,33 Furthermore, increased ROS concomitantly decreases the work functionality of renal system. 16,33 Altered glomerular ltration rate or deterioration in renal function was reected by the increase in BUN and creatinine, as well as the occurrence of microproteinuria.…”
mentioning
confidence: 99%
“…16,31,33 Furthermore, increased ROS concomitantly decreases the work functionality of renal system. 16,33 Altered glomerular ltration rate or deterioration in renal function was reected by the increase in BUN and creatinine, as well as the occurrence of microproteinuria. 16,33 The alcohol/disulram-induced deleterious effects on the renal system were indicated by the increased level of serum BUN, creatinine and the occurrence of microproteinuria.…”
mentioning
confidence: 99%
See 1 more Smart Citation